Mobile Learning Development in Security Intelligence Technical Functions Courses for Police Academy Cadets - Wita Puspitasari; Eveline Siregar; Robinson Situmorang (Peneliti.net, 2020)
This research is based on the fact that most Akpol Cadets have difficulty in understanding the materials at the subject of Security Intelligence Technical Functions. This is because of the many foreign terms in intelligence that are quite difficult to understand. In addition, it is also caused by the limitations of teaching materials that exist today in loading visual images or illustrations that can facilitate Akpol Cadet in understanding the material. This research aims to produce mobile learning in the Security Intelligence Technical Functions as a source of learning that is of high innovation value so that cadets can learn the subject matter of Security Intelligence Technical Functions more easily and gain more real experience of technical learning materials, and the learning process can become more effective because Akpol Cadets can re-review the learning materials outside the learning process. This research will apply Research and Development (R & D) method using Dick and Carey research and development model, while for product development model to be done using Hannafin and Peck model at the learning material development stage.